Moisture absorption and thickness swelling behaviour of luffa fibre/epoxy composite. (October 2019) - Bera, Tanusree; Mohanta, Niharika; Prakash, Ved; Pradhan, Subhrajit; Acharya, Samir K
The present work aims to study the moisture uptake and thickness swelling behaviour and its effect on tensile and flexural properties of Luffa cylindrica epoxy composite. Characterizations of the luffa fibre surface were carried out by energy-dispersive X-ray spectroscopy and Fourier transform infrared spectroscopy. Composites were casted with single, double and triple layer of Luffa cylindrica fibre reinforced with epoxy resin by general hand-layup technique. Moisture uptake tests of composites were conducted by subjecting the composite samples in three different environments such as distilled water, saltwater (5% NaCl solution) and sub-zero temperature (–25°C). The diffusivity constant, thickness swelling rate parameter ( KSR ) and equilibrium moisture content were found out. The result indicates that moisture absorption pattern follows the Fickian diffusion behaviour for composites in all three environments. As the fibre layer increases, the percentage of moisture uptake increased due to high cellulose content. The mechanical properties of the composites were decreased with moisture absorption. Scanning electron microscope study was carried out to study the fracture behaviour of tested samples.